2012
DOI: 10.4102/sajpsychiatry.v18i4.368
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning and associated factors in older adults in South Africa

Abstract: Cognition can be divided into domains of ability including orientation, memory, executive function and language.1 Cognitive function is influenced by many factors such as genes, home environment in childhood, education and occupation.1 Cognitive decline is first detectable in the fifth decade of life, with age-related decline from this point onwards.2 There is little research on cognitive functioning and variability among older adults in South Africa. In various cross-sectional and longitudinal studies, better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
7
14
1
Order By: Relevance
“…Participants who sat for fewer than 2 hours per day were more likely to practice physical activity than those sitting more than 2 hours per day. This result was similar with study done in South Africa26 and Nigeria 27 28. The reason is that participants sitting less can spent more time in active tasks that can assist them for physical activity practice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Participants who sat for fewer than 2 hours per day were more likely to practice physical activity than those sitting more than 2 hours per day. This result was similar with study done in South Africa26 and Nigeria 27 28. The reason is that participants sitting less can spent more time in active tasks that can assist them for physical activity practice.…”
Section: Discussionsupporting
confidence: 90%
“…Evidence shown that different factors were associated with attaining physical activity guideline. For instance, sociodemographic factor (sex, age, educational status, occupation and income) and other factors like knowledge of physical activity guideline, satisfaction with current level of physical activity, future intentions to engage in physical activity and sitting time in day were associated with physical activity participation 5–29. There has been limited study on knowledge of physical activity guideline and its participation in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…These findings compare with other SAGE publications examining cognition in Ghana, Tanzania, India ( 18 ), South Africa ( 22 ), and China ( 23 ), where poorer cognitive function was observed in those of advancing age, rural living, lower education, and wealth levels, and poorer subjective health status, including deterioration in ADLs and slower gait. Subjective losses in memory and daily functioning and its association with poorer cognition have been described as features of mild cognitive impairment ( 6 , 7 ), and testing these along with gait speed ( 24 ) may aid the early detection of those at high risk of dementia and provide a point for successful interventions.…”
Section: Discussionsupporting
confidence: 78%
“…Existing evidence demonstrates that educational attainment is strongly associated with cognitive function among older adults in South Africa (Humphreys et al, 2017; Peltzer and Phaswana-Mafuya, 2012). However, given that Bantu schooling in Apartheid South Africa was of very poor quality, there may be early-life factors that would influence both of one’s educational attainment and their later-life cognitive health.…”
Section: Introductionmentioning
confidence: 99%